(untitled) (Texas Journal of Philology, Culture and History, 2022)
In this article, phraseological units expressing character in French and Uzbek languages are analyzed from a theoretical point of view. In most of the studies conducted in the field of linguistics, ideas about the unity of language and culture are leading. In fact, it is more correct to evaluate the communication between people speaking two languages not only as an exchange of information through language, but also as a communication between two people’s cultures. It is for this reason that in recent times there has been an increasing interest among scientists to study the function of cultural information exchange of phraseology, that is, the tasks of reflecting the worldview and experiences of several generations in the field of knowledge of the world in the semantic structure of phraseology